Genocide and resistance Nr. 29(1) - Buchaveckas, Stanislovas; Zagreckas, Rimantas; Jokubauskas, Vytautas; Bubnys, Arūnas; Burinskaitė, Kristina; Okuličiūtė, Lina; Dabrovolskas, Audrius; Vasiliauskienė, Aldona (Genocidas ir rezistencija, 2011)
Full Issue